KUALITAS BACAAN SURAH AL-FᾹTIḤAH IBU RUMAH TANGGA: (STUDI LIVING QUR’AN DI KELURAHAN GONDRONG, KOTA TANGGERANG) - Mawaddah, Amelia; Ulinnuha, Muhammad (STAI Asy-Syukriyyah, 2024)
In reciting the Al-Qur'an, it must be accompanied by quality recitation and tartil because it is a direct command from Allah SWT through his word in surah Al-Muzammil verse 4 which reads